Venoms of Rear-Fanged Snakes: New Proteins and Novel Activities - Modahl, Cassandra M.; Mackessy, Stephen P. (Frontiers in Ecology and Evolution, 2019)
Snake venom research has focused on front-fanged venomous snakes because of the high incidence of human morbidity and mortality from envenomations and larger venom yields of these species, while venoms from rear-fanged snakes have been largely neglected. Rear-fanged snakes (RFS) are a phylogenetically diverse collection of species that feed on a variety of prey and show varying prey capture strategies, from constriction to envenomation. In general, RFS venoms share many toxin families with front-fanged snakes, and venoms generally are either a neurotoxic three-finger toxin (3FTx)-dominated venom or an enzymatic metalloproteinase-dominated venom. These venoms have also been discovered to contain several unique venom protein families. New venom protein superfamilies in RFS venoms include matrix metalloproteinases, distinct from but closely related to snake venom metalloproteinases, veficolins, and acid lipases. Specialized three-finger toxins that target select prey taxa have evolved in some RFS venoms, and this prey capture strategy has appeared in multiple RFS species, from Old World Boiga to New World Spilotes and Oxybelis. Though this same protein superfamily is commonly found in the venoms of elapid (front-fanged) snakes, no elapid 3FTxs appear to show prey-specific toxicity (with the exception of perhaps Micrurus). Neofunctionalization of Spilotes sulphureus 3FTx genes has even resulted in the evolution within a single venom of 3FTxs selectively neurotoxic to different prey taxa (mammals or lizards), allowing this non-constricting RFS to take larger mammalian prey. The large number of 3FTx protein sequences available, together with a growing database of RFS venom 3FTxs, make possible predictions concerning structure-function relationships among these toxins and the basis of selective toxicity of specific RFS venom 3FTxs. Rear-fanged snake venoms are therefore of considerable research interest due to the evolutionary novelties they contain, providing insights into the evolution of snake venom proteins and potential predator-prey coevolution in a broader phylogenetic context. Because of the limited complexity of these venoms, they represent a more tractable source to inform about the biological roles of specific venom proteins that are found in the venoms of this rich diversity of snakes.